Crescimento, desenvolvimento e produtividade de clones avançados de batata em cultivo de primavera e de outono em ambiente subtropical - Zanon, Alencar Junior (2011)
The objectives of this dissertation were to determine the phyllochron, the final leaf number on the main stem and the duration of developmental stages to characterize leaf growth during the developmental cycle and to determine the tuber yield of tenadvanced potato clones of the Potato Breeding and Genetics Program of the Universidade Federal de Santa Maria (UFSM) and two potato cultivars grown in spring and fall conditions in Santa Maria, Depression Central Region of the Rio Grande do Sul State. Two field experiments were conducted during Spring 2010 and Fall 2011 at the experimental field of the, Santa Maria, RS. The advanced potato clones were: SMINIA 00017-6, SMINIA 793101-3, SMINIA 02106-11, SJSM 00211-3, SJSM 03478-37, SJSM 01212-2, SJSM 01274-4, SJSM 04503-9, SJSM 02349 - 1 and SJSM 02317-3. The two potato cultivars were Asterix and Macaca. The planting density was 3.79 hills m-2. The experiment was a complete randomized block design with seven replications. After emergence, four plants in each plot were marked and on these plants the number of leaves on the main stem were counted twice a week and on one of these plants the length of the leaves was measured once a week to determine the green leaf area index. Tuber initiation was determined by collecting four plants of each clone at the border rows. The phyllochron was calculated by the inverse of the slope of the linear regression between leaf number and accumulated thermal time. Power-like nonlinear models were used to relate leaf length and leaf area. For determining tuber yield all the hills were used. The phyllochron varied from 17.0°C to 21.5°C day leaf the in Spring and from 14.8°C to 22.1° C in the Fall. There are differences of the duration of vegetative and tuberization phases and the final leaf number among clones, cultivars and growing seasons. The evolution of leaf area index throughout the developmental cycle was different in the advanced clones and in the cultivars during the two growing seasons. The of advanced clones showed high tuber yield in both Spring and Fall growing seasons.